Recent advances in date palm genomics: A comprehensive review - Rahman, Hifzur; Vikram, Prashant; Hammami, Zied; Singh, Rakesh Kumar (Frontiers in Genetics, 2022)
Date palm (Phoenix dactylifera) is one of the oldest fruit trees in the Middle East and North African peninsula and is highly relevant for the region's economy. It has been placed on UNESCO's list of Intangible Cultural Heritage of Humanity. Believed to be the first tree to be cultivated by humans, date palm was probably harvested for its fruit nearly 7000 years ago. Initial research efforts on date palm genetics were focused on understanding the genetic diversity of date palm germplasm collections and the phylogenetic history, which are important prerequisites for its improvement. Despite several studies, the center of origin of date palm is still unclear; however, genomic studies suggest two probable domestication events in date palm, one in the Middle East and the other in North Africa, consisting of two separate gene pools. The current review covers the studies related to the omics analyses conducted to decipher the existing genetic diversity of date palm. With advances and cost reductions in sequencing technologies, rapid progress has been made in the past few years in date palm genomics research. Along with organellar genomes, several reference genomes of date palm are now available. In addition, several genotypes have been resequenced either to detect single nucleotide polymorphisms (SNPs) or to study domestication and identification of key genes/loci associated with important agronomic traits such as sex, fruit color, and sugar composition. This genomics research progress has paved the way to carrying out fast-track and precise germplasm improvement processes in date palm. In this article, we have reviewed the advances made in genetics and genomics in date palm to strategize targeted crop improvement plans for marginal areas of the Middle East, North African peninsula, and other parts of the world.